IDENTIFIKASI VEGETASI TUMBUHAN DI KAWASAN MATING RING KUAU RAJA (Argusianus argus) DI STASIUN PENELITIAN SORAYA, KAWASAN EKOSISTEM LEUSER, KOTA SUBULUSSALAM - Furida, Asra; Hidayat, Muslich (KENANGA : Journal of Biological Sciences and Applied Biology, 2025)
The presence of mating rings of the Great Argus (Argusianus argus) is strongly influenced by vegetation structure and surrounding environmental conditions. However, scientific studies focusing on vegetation characteristics associated with mating ring sites remain limited. This study aimed to identify the composition of plant vegetation and environmental factors surrounding the mating rings of the Great Argus at the Soraya Research Station, Leuser Ecosystem Area, Subulussalam City. Data were collected using roaming surveys and purposive sampling at eight mating ring sites. Vegetation analysis was conducted using a 100 × 100 m main plot with four subplots representing tree, pole, sapling, and understory strata. Environmental parameters measured included air and soil temperature, humidity, light intensity, soil pH, elevation, slope, diameter at breast height (DBH), and mating ring diameter. The results recorded 1,229 individual plants comprising 147 species from 36 families. Dominant vegetation consistently found across most mating ring sites included Shorea multiflora, Sloetia elongata, Croton argyratus, and Gironniera subaequalis. These vegetation types generally formed moderately open canopies with local microclimatic conditions characterized by moderate light intensity, high humidity, and near-neutral soil pH. The findings indicate that vegetation structure and microhabitat conditions play an important role in supporting the formation of mating rings of the Great Argus. This study provides essential baseline ecological data to support habitat management and conservation efforts for the Great Argus within the Leuser Ecosystem.  Keywords:  Great Argus (Argusianus argus), Mating Ring, Vegetation, Soraya Research Station